Quality system for POCT: Point of care testing. - Pichitchok, Y. (Chulalongkorn Medical Journal, 2023)
Point of care testing (POCT) increases the efficiency of care. Quality and accuracy of the analysis is very important. Implementation of POCT without any system of quality management may affect both the quality of care and patient safety. Errors in the analysis can occur in the process : pre-analytic, analytic, and post-analytic. International standard that had been used for POCT is ISO 22870:2006. Requirements of standard compose of 14 management requirements and 8 technical requirements.